Osteal macrophages support osteoclast‐mediated resorption and contribute to bone pathology in a postmenopausal osteoporosis mouse model. (3rd August 2021) - Batoon, Lena; Millard, Susan M.; Raggatt, Liza J.; Wu, Andy C.; Kaur, Simranpreet; Sun, Lucas W.H.; Williams, Kyle; Sandrock, Cheyenne; Ng, Pei Ying; Irvine, Katharine M.; Bartnikowski, Michal; Glatt, Vaida; et al.
ABSTRACT: Osteal macrophages (osteomacs) support osteoblast function and promote bone anabolism, but their contribution to osteoporosis has not been explored. Although mouse ovariectomy (OVX) models have been repeatedly used, variation in strain, experimental design and assessment modalities have contributed to no single model being confirmed as comprehensively replicating the full gamut of osteoporosis pathological manifestations. We validated an OVX model in adult C3H/HeJ mice and demonstrated that it presents with human postmenopausal osteoporosis features with reduced bone volume in axial and appendicular bone and bone loss in both trabecular and cortical bone including increased cortical porosity. Bone loss was associated with increased osteoclasts on trabecular and endocortical bone and decreased osteoblasts on trabecular bone. Importantly, this OVX model was characterized by delayed fracture healing. Using this validated model, we demonstrated that osteomacs are increased post‐OVX on both trabecular and endocortical bone. Dual F4/80 (pan‐macrophage marker) and tartrate‐resistant acid phosphatase (TRAP) staining revealed osteomacs frequently located near TRAP + osteoclasts and contained TRAP + intracellular vesicles. Using an in vivo inducible macrophage depletion model that does not simultaneously deplete osteoclasts, we observed that osteomac loss was associated with elevated extracellular TRAP in bone marrow interstitium and increased serum TRAP. Using in vitro high‐resolution confocal imaging of mixed osteoclast‐macrophage cultures on bone substrate, we observed macrophages juxtaposed to osteoclast basolateral functional secretory domains scavenging degraded bone byproducts. These data demonstrate a role for osteomacs in supporting osteoclastic bone resorption through phagocytosis and sequestration of resorption byproducts. Overall, our data expose a novel role for osteomacs in supporting osteoclast function and provide the first evidence of their involvement in osteoporosis pathogenesis. © 2021 American Society for Bone and Mineral Research (ASBMR).